Determination of Serum Zinc Concentration in SGA Neonates as Compared to AGA Neonates - Maninder Kaur; Singh J; Gupta M; Kaur D (GMC Patiala Journal of Research and Medical Education, 2018)
Birth weight is the single most important determinant of infant survival in developing countries. Low birth weight is associated with poor subsequent growth in infancy and childhood with increased morbidity from infectious diseases and compromised congnitive and behavioural development. Zinc is required to maintain the normal structure and function of multiple enzymes including those that are involved in transcription and translation of genetic material and cell division and growth and development. In our study Serum Zinc levels were compared in small for gestational age babies with respect to appropriate for gestational age babies. It was found that maternal Zinc levels affect the weight of the baby. So Zinc supplements during pregnancy lead to normal birth weight babies.